2022
DOI: 10.14348/molcells.2022.2257
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of the Habenula in Rats Exposed to Chronic Restraint Stress

Abstract: Chronic stress contributes to the risk of developing depression; the habenula, a nucleus in epithalamus, is associated with many neuropsychiatric disorders. Using genome-wide gene expression analysis, we analyzed the transcriptome of the habenula in rats exposed to chronic restraint stress for 14 days. We identified 379 differentially expressed genes (DEGs) that were affected by chronic stress. These genes were enriched in neuroactive ligand-receptor interaction, the cAMP (cyclic adenosine monophosphate) signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Such findings are contrary to the observations in human patients and mice that undergo other stress paradigms ( Stetler and Miller, 2011 ). Recent findings have identified the effects that CRS shares with other paradigms and that mirror those observed in humans ( Yuen et al, 2012 ; Seewoo et al, 2020 ; Yoo et al, 2022 ). For example both CRS and CSDS induce elevated firing in the projection from the lateral hypothalamus to the LHb which causes the onset of depressive-like symptoms ( Zheng et al, 2022 ).…”
Section: Modelling Pathogenesismentioning
confidence: 83%
“…Such findings are contrary to the observations in human patients and mice that undergo other stress paradigms ( Stetler and Miller, 2011 ). Recent findings have identified the effects that CRS shares with other paradigms and that mirror those observed in humans ( Yuen et al, 2012 ; Seewoo et al, 2020 ; Yoo et al, 2022 ). For example both CRS and CSDS induce elevated firing in the projection from the lateral hypothalamus to the LHb which causes the onset of depressive-like symptoms ( Zheng et al, 2022 ).…”
Section: Modelling Pathogenesismentioning
confidence: 83%
“…Gok Oguz et al analyzed the apelin level in peritoneal dialysis (PD) patients with depression and anxiety and found that it was significantly greater than that in PD patients without depression and anxiety (Gok Oguz et al, 2016). A previous study also revealed DEGs related to neuroactive ligand-receptor interactions in a chronic restraint stress (CRS) rat model (Yoo et al, 2022). The calcium signaling pathway was also enriched in CUMS models and depression patients (Kao et al, 2012;Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Stress has negative effects on both the neuroendocrine system and the sympathetic nervous system (SNS) of the body, which is manifested by continuous activation of the hypothalamic–pituitary–adrenal (HPA) axis and SNS, thus increasing catecholamine secretion, promoting tumor cell proliferation and metastasis, and enhancing angiogenesis 29 , 32 , 33 . Neuroactive ligand-receptor interactions are thought to be a key factor involved in emotion-related disorders 34 36 , and stress runs through these disorders. Wen et al found that oxidative stress is involved in the pathogenesis process of PTC 37 .…”
Section: Discussionmentioning
confidence: 99%